Sijakar Alat Bantu Penangkap Ikan Modern Bagi Nelayan Tambak Lorok Semarang - Sutini Sutini; Yulianto Yulianto; Dhanan Abimanto; Dedy Rusmiyanto (Jurnal Informasi Pengabdian Masyarakat, 2023)
Fishing is a fishing activity that has been around for a long time. Fishing is done to fulfill human needs. Based on existing data, Indonesian people's consumption of fish reaches an average of 41 kilograms per capita per year, in other words, it is still very low. One of the causes is the lack of productivity of fish catches. Fishing is dominated by large vessels with modern equipment, so the fishing capacity of traditional fishermen is very low. The Ministry of Maritime Affairs and Fisheries is trying to increase fishing productivity, one of which is by providing fishing deck machinery to small fishermen. The problem is that fishing aids are imported products and require maintenance which is not easy and not cheap. Based on this, a fishing tool that is more efficient and easy to maintain and operate is designed. The process of fishing aids uses a buoy equipped with AIS. The purpose of the buoy frequency for calling fish is equipped with AIS which is used to detect the position of the buoy for 2 to 4 days when the ship will come to take the buoy. It is installed on the buoy, namely to maintain security and call fish. The signal from the buoy uses the frequency on the buoy which is used to catching fish is also to detect other ships that will approach to catch fish and where there are lots of fish. The Ulrich and Eppinger method with the mission of fishing aid products can be made by local industry. Based on the results of the product concept design for fishing aids, the 1st (one) variant concept was chosen with specifications, namely: (1) tool dimensions 500 mm x 150 mm x 225 mm; (2) a drive system with low electrical power using a large reducer rotation; (3) has 2 (two) manual functions and functions